Sensory characteristics and volatile compounds of beef in feedlots with cottonseed - COUTO, Claudiana Esteves; BRUHN, Fabio Raphael Pascoti; SANTOS, Leandro Soares; LIMA, Lidiany Mendonça Zacaroni; FARIA, Peter Bitencourt (Food Science and Technology, 2024)
The aim of this study was to evaluate the sensory characteristics of meat from cattle fed a cottonseed diet. A total of 100 beef cattle, with a mean initial live weight of 386.19 ± 4.48 kg and a mean slaughter weight of 527.82 ± 17.96 kg, aged between 13 and 48 months, were maintained in the feedlot for 88 days. This study was conducted with two treatments: a control treatment and feeding cattle whole cottonseed at a concentration of 15.9%. The animals were slaughtered for determination of sensory and volatile compounds in the beef. There was a difference in aroma, with better grades attributed to beef not fed cottonseed. The use of cottonseed promoted the occurrence of a strange taste in beef. There was a difference in the profile of volatile compounds between the groups. In general, feeding cattle cottonseed did not modify the qualitative sensorial aspects of beef; however, there was a greater chance of the development of some strange flavors of high intensity. The volatile compound profile of beef from cattle fed cottonseed was different than that of beef from control group.